Age-related changes in cell surface antigens of preleukemic AKR thymocytes (The Rockefeller University Press, 1976)
Thymocytes from preleukemic AKR mice aged 5-6 mo have an altered pattern of cell surface antigens. The expression of four MuLV-related antigens on the cell surface (GIX, GCSA, gp70, p30) is markedly increased in comparison to 2-mo-old AKR mice and approximates the heightened levels of these antigens found on thymic leukemia cells. H-2 and Thy-1 alloantigens also show characteristic modifications in relation to age and leukemia development. In contrast to the high Thy- 1/low H-2 levels on 2-mo-old AKR thymocytes, thymocytes from 6-mo-old mice and thymic leukemia cells frequently show a low Thy-1/high H-2 surface phenotype. As thymocytes from mouse strains with a low incidence of leukemia do not show these changes, they appear to represent a stage in the conversion of normal cells to leukemia cells.